2014
DOI: 10.1039/c4ta03805c
|View full text |Cite
|
Sign up to set email alerts
|

Array geometry dictates electrochemical performance of Ge nanowire lithium ion battery anodes

Abstract: Scientific literature shows a substantial study-to-study variation in the electrochemical lithiation performance of “1-D” nanomaterials such as Si and Ge nanowires or nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 116 publications
1
16
0
Order By: Relevance
“…Moreover, we have reported the detailed structure of the wrinkled Si framework to elucidate its high performance 21 . The formation of similar structures to the wrinkled structure have been reported in the Si nanowires 24 and carbon nanotube covered by Si nanolayer 25 , and also in Ge 26 27 28 29 30 31 32 33 34 and SnO 2 35 , which involve large volume expansion/contraction upon lithiation/delithiation. In these examples, the presence of a continuous framework consisting of a nano-sized active material (Si, Ge, or SnO 2 ) is the key factor for the formation of the wrinkled structure, thereby exhibiting a high performance.…”
supporting
confidence: 67%
“…Moreover, we have reported the detailed structure of the wrinkled Si framework to elucidate its high performance 21 . The formation of similar structures to the wrinkled structure have been reported in the Si nanowires 24 and carbon nanotube covered by Si nanolayer 25 , and also in Ge 26 27 28 29 30 31 32 33 34 and SnO 2 35 , which involve large volume expansion/contraction upon lithiation/delithiation. In these examples, the presence of a continuous framework consisting of a nano-sized active material (Si, Ge, or SnO 2 ) is the key factor for the formation of the wrinkled structure, thereby exhibiting a high performance.…”
supporting
confidence: 67%
“…Meanwhile, TiO 2 nanowires were fabricated through a self-scrolling and template-free process by Li et al and reversible specific capacity of 153 mAh g À1 was remained after 300 cycles at 10 C [17]. Farbod et al successfully synthesized the Ge nanowire, which was highly favorable in terms of the reversible capacity, and high-rate capability [18]. All these results have demonstrated that construction of active materials with1D nanotubes and nanowires is a good way to improve the electrochemical properties of electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…When C 1s spectra were fitted, many kinds of carbon functional groups were observed, such as C–O (286.0 eV), CO (287.4 eV), and CO­(RCOOR′) (289.3 eV), providing spectroscopic evidence of electrolyte decomposition. In the F 1s spectra, peaks assigned to LiF (685.4 eV), Li x PO y F z (687.3 eV), and Li x PF y (688.5 eV) were commonly observed in cycled cathodes. Although quantitative analyses indicated that the amount of F element was almost the same for cycled h-LNCM and 0.3-TSO h-LNCM cathodes, relatively large amounts of LiF and Li x PF y (which were considered decomposed components increasing the internal resistance of the cell) formed in the cycled h-LNCM cathode.…”
Section: Resultsmentioning
confidence: 99%